Influence of Liquidity and Profitability on Profits Growth of Nigerian Pharmaceutical Firms - Odukwu Victory Chika; Eke Promise; Igwoba Solomon U; Egule Victoria Werikum (Penerbit Goodwood, 2022)
Purpose: This study sought to assess the influence of liquidity ratio and profitability ratio on profit growth of pharmaceutical firms in Nigeria. Method: The researcher employed ex-post facto research strategy with a population of six (6) selected listed pharmaceutical firms in Nigerian stock exchange market. The study used 30 firm yearly observations from the six pharmaceutical firms listed in Nigeria. Results: The results of the study revealed that the current ratio's liquidity ratio and the quick ratio's liquidity ratio had a statistically significant link with profit growth rate. The profit growth rate has no statistically significant link with the profitability ratio of net profit margin and return on asset. Limitations: The discoveries of this study is limited to pharmaceutical firms in Nigeria and may not be adopted elsewhere. Contribution: This study is anticipated to help pharmaceutical companies manage their cash and cash equivalents while also improving the performance of the business.